Improving Students’ Knowledge of Biomonitoring through Service Learning in Higher Education Institution - Eka Sulistiyowati; Dien F. Awaliyah; Shofwatul Uyun (Universitas Nurul Jadid, 2025)
Service learning in biomonitoring is urgent as it links science with community action to tackle river health issues.. This research aims to explore the application of service learning in enhancing students' knowledge and their ability to carry out river health biomonitoring projects. The study involved students in implementing the service learning curriculum through stages of planning, execution, reflection, and assessment. During the planning phase, students participated in developing the module. The results indicated that the biomonitoring module received a quality score of 3.8, with clarity of content and factual accuracy achieving the highest scores (4.0). The service learning program was conducted through the establishment of ECOFOREST groups, training sessions, and the application of action plans within the community. The effectiveness was measured using a one-group pretest-posttest design, which revealed a significant improvement in student understanding (t(22) = 2.45, p < 0.05). These findings confirm that service learning not only enhances student engagement in the community but also contributes to their technical competency development. This study addresses the gap in literature regarding service learning within more practical experiential learning frameworks in higher education.The result implies that there has been an increase of knowledge among the participants.